2005
DOI: 10.1093/brain/awh603
|View full text |Cite
|
Sign up to set email alerts
|

Sepiapterin reductase deficiency: a congenital dopa-responsive motor and cognitive disorder

Abstract: This study presents the clinical findings on seven children from Malta (population 385,000). All of them had early motor delay and a significant degree of cognitive impairment. Diurnal variation of the motor impairments was clear in six out of seven of the subjects and oculogyric crises occurred from an early stage also in six out of the seven. Five out of seven had clear evidence of dystonia but the early picture was dominated by hypotonia in five. Two had early Parkinsonian tremor and chorea was seen in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 11 publications
0
65
0
1
Order By: Relevance
“…The phenotype of SR deficiency is mainly characterized by an affection of the motor and cognitive system. Patients exhibit psychomotor retardation and neurologic symptoms dominated by axial muscular hypotonia, dystonic movements, spasticity, and parkinsonism with diurnal fluctuation (Abeling et al 2006;Dill et al 2012;Neville et al 2005). In infancy, muscular hypotonia and developmental delay are usually the only clinical findings.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of SR deficiency is mainly characterized by an affection of the motor and cognitive system. Patients exhibit psychomotor retardation and neurologic symptoms dominated by axial muscular hypotonia, dystonic movements, spasticity, and parkinsonism with diurnal fluctuation (Abeling et al 2006;Dill et al 2012;Neville et al 2005). In infancy, muscular hypotonia and developmental delay are usually the only clinical findings.…”
Section: Discussionmentioning
confidence: 99%
“…Patients exhibit psychomotor retardation, inconsolable crying, neurological abnormalities (hypotonia, dystonic posturing, oculogyric crises, spasticity, tremor, ataxia, gait disorder, chorea, Parkinsonism, seizure-like movements), psychiatric symptoms (depressed affect, aggressive behavior, hypersomnolence), and occasional physical findings (microcephaly, growth deficiency) (Abeling et al 2006, Neville et al 2005. As with other dopa-responsive disorders, symptoms are characteristically worse in the evenings, so-called diurnal variation.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the disorders that respond to levodopa are termed dopa-responsive dystonias (DRD), the best known being GTP cyclohydrolase deficiency (Segawa's disease). In addition, defects in tyrosine hydroxylase, aromatic L-amino acid decarboxylase and sepiapterin reductase (SR) can also lead to DRD (Zorzi et al 2002;Friedman et al 2006; Th€ ony and Blau 2006; Abeling et al 2006;Neville et al 2005). No association with peroxisomal disorders has ever been described.…”
Section: Introductionmentioning
confidence: 99%
“…(Bonafé et al, 2001) Many of patients were reported around Mediterranean. (Neville et al, 2005) Sepiapterin reductase is one of enzymes to covert sepiapterin into BH4. (See Fig.2) Patients from Malta showed early motor delay and a significant degree of cognitive impairment.…”
Section: Sepiapterin Reductase (Sr) Deficiencymentioning
confidence: 99%
“…Initial dose of L-dopa was 1.5 to 4 mg/kg/day (12.5 to 50 mg/day). (Neville et al, 2005) In these patients, 100 mg L-dopa and 10 mg Carbidopa tablets were used. One case report described incomplete response to treatment during short-term follow-up.…”
Section: Sepiapterin Reductase (Sr) Deficiencymentioning
confidence: 99%